Molecular and Biochemical Characterization of the Greek Pepper ( Capsicum annuum ) Cultivars ‘Florinis’ and ‘Karatzova’ - Niki Mougiou (Polish Journal of Food and Nutrition Sciences, 2021)
Peppers are the fourth most important vegetable in the global food economy. Greek pepper cultivars ‘Florinis’ and ‘Karatzova’ are especially popular because of the signature red color and sweet taste of the fruits. The economic interest in ‘Florinis’ peppers has led to many adulteration events. In that aspect, genetic profiles of ‘Florinis’, a ‘Florinis’-type and ‘Karatzova’ peppers, were studied using Inter Simple Sequence Repeats (ISSR) molecular markers and an automated fragment detection system. Biochemical parameters, such as total dietary fiber, total phenolic and lycopene contents, and sugar profile that affect the fruit organoleptic and nutritional properties were evaluated. The molecular protocol established during this study may successfully discriminate the original ‘Florinis’ cultivar from the ‘Florinis’-type peppers. ‘Karatzova’ cultivar, which fruits are similar to ‘Florinis’, presented also a unique profile. The biochemical evaluation revealed that ‘Florinis’ peppers had the highest sweetness index and total phenolic content. Such an analysis could be used for the discrimination of pepper cultivars sharing common morphological traits ensuring the unique identity of each cultivar and protecting farmers and consumers from fraud.